PENENTUAN EFEKTIVITAS METODE PELAKSANAAN PADA PROYEK PERKERASAN JALAN KAKU (RIGID PAVEMENT) DI BOJONEGORO - Rahmawati, Alfia Nur; Mustofa, Muhammad Amirul (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
Construction of a road with a rigid pavement type requires a longer time than a flexible or asphalt pavement, as a result of the length of time the work will pose several risks, one of which is causing congestion, for this reason, in road construction, it is necessary to consider the method used in its implementation whether it is a continuous or non-continuous system and still considers quality, time and cost. The purpose of the research is to 1). Identify what are the advantages and disadvantages of each method used in the implementation of rigid pavement, and 2). Analyzing what method is more effective in implementing the construction of rigid pavements which will be analyzed using the Analytical Hierarchy Process (AHP) method. The benefit of this research is that it can contribute as a reference in making decisions on the method of implementing the next project. The output of this research is the publication of the Sinta 6 National journal in the Civil Engineering Project Journal.